Short-chain L-3-hydroxyacyl-CoA dehydrogenase: A novel vital oncogene or tumor suppressor gene in cancers - Fang, He; Li, Hanyang; Zhang, Hang; Wang, Shu; Xu, Shuang; Chang, Li; Yang, Yongsheng; Cui, Ranji (Frontiers in Pharmacology, 2022)
The reprogramming of cellular metabolism is frequently linked to tumorigenesis. Glucose, fatty acids, and amino acids are the substrates that help an organism maintain metabolic equilibrium. The HADH gene codes for the short-chain L-3-hydroxyacyl-CoA dehydrogenase (HADH), a crucial enzyme in fatty acid oxidation that catalyzes the third phase of fatty acid oxidation in mitochondria. Increasing data suggests that HADH is expressed differently in various types of malignancies and is linked to carcinogenesis and progression. The significance of HADH in malignancies and probable mechanisms of action of HADH in the onset and progression of certain cancers are summarized in this article. The role of HADH as a possible target for the detection and therapy of various malignancies is investigated in this article.